The mediating role of job satisfaction and presenteeism on the relationship between job stress and turnover intention among primary health care workers - Liangwen Ning; Huanhuan Jia; Shang Gao; Minghui Liu; Jiaying Xu; Sangyangji Ge; Ming Li; Xihe Yu (BMC, 2023)
Abstract Background Turnover problems among primary health care workers are a significant contributor to the shortage of health human resources. This study aims to determine the relationship between job stress and turnover intention among primary health care workers, as well as to examine the mediating effects of job satisfaction and presenteeism on this relationship. Methods Stratified random sampling and quota sampling were used to select 703 primary health care workers in Jilin Province, China in January 2020. Validated scales were used to measure turnover intention, job stress, job satisfaction, and presenteeism among primary health care workers. The study utilized a partial least squares structural equation modeling (PLS-SEM) approach to test the research hypotheses. Results The turnover intention score of primary health care workers in Jilin Province was 2.15 ± 1.03, and 19.5% of respondents reported a higher turnover intention. Significant sex and occupation differences were found, with a higher rate of turnover intention for male and doctor groups among primary health care workers. This study also revealed a positive correlation between job stress and turnover intention (β = 0.235, P < 0.001), a significant negative correlation between job satisfaction and turnover intention (β= -0.347, P < 0.001), and a significant positive correlation between presenteeism and turnover intention (β = 0.153, P < 0.001). Moreover, the study revealed a significant indirect effect of job stress on turnover intention which was mediated by job satisfaction (β = 0.183, P < 0.001) and presenteeism (β = 0.078, P < 0.001). Conclusion We confirmed the positive association between job stress and presenteeism with turnover intention, as well as the negative association between job satisfaction and turnover intention. Moreover, our study confirmed the mediating role of job satisfaction and presenteeism in the relationship between job stress and turnover intention. This study provides scientific evidence to address the turnover problem among primary health care workers.